Monitoring the effect of chlorine on the ageing of polypropylene pipes by infrared microscopy. (January 2015) - Damodaran, Subin; Schuster, Tobias; Rode, Karsten; Sanoria, Abhishek; Brüll, Robert; Wenzel, Mirko; Bastian, Martin
Abstract: The effect of hot water and chlorinated water at 95 °C on differently nucleated random polypropylene pipes was analysed with respect to the chemical changes occurring to the polymer and antioxidants (AOs). Infrared microscopy (μFT-IR) was used to monitor the loss of the AOs as well as to identify their degradation products during ageing. For the quantification of the primary AO, 1, 3, 5-Tris (3, 5-di-tert-butyl-4-hydroxybenzyl)-2, 4, 6-methylbenzene (AO-13) in a mixture with Pentaerythritol tetrakis (3-3, 5-di-tert-butyl-4-hydroxyphenyl) propionate (AO-18) and the processing stabiliser tris(2, 4-di-tert-butylphenyl) phosphate (PS-2) in PP-R, a new μFT-IR method has been developed and the results were supported by extraction → HPLC. Degradation products of phenolic AOs were profiled for the first time across the pipe wall using μFT-IR. Time and space resolved content of AO-18 and AO-13 left in the pipes with time was quantified. For both ageing conditions, AO-18 and AO-13 exhibited a bilateral loss from the wall of PP-R1 whereas in PP-R2, the loss was mainly unidirectional. Oxidative induction time (OIT) measurements of mechanically prepared samples across the pipe wall also validate the bilateral and unidirectional loss profiles of AOs. The loss in average molar mass of the polymer as a result of chain scission was analysed by gel permeation chromatography. The linear relations drawn for molar mass against the relative content of AOs explain that the deterioration of the pipes was accelerated with chlorinated water. From the substantial differences in the AO loss coefficients which were calculated using μFT-IR, it can be speculated that nucleation of the PP-R exerts an influence on the depletion of AOs.